2004
DOI: 10.1128/aem.70.8.4449-4457.2004
|View full text |Cite
|
Sign up to set email alerts
|

Benzoic Acid, a Weak Organic Acid Food Preservative, Exerts Specific Effects on Intracellular Membrane Trafficking Pathways in Saccharomyces cerevisiae

Abstract: Microbial spoilage of food causes losses of up to 40% of all food grown for human consumption worldwide. Yeast growth is a major factor in the spoilage of foods and beverages that are characterized by a high sugar content, low pH, and low water activity, and it is a significant economic problem. While growth of spoilage yeasts such as Zygosaccharomyces bailii and Saccharomyces cerevisiae can usually be retarded by weak organic acid preservatives, the inhibition often requires levels of preservative that are ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 53 publications
(71 reference statements)
0
74
1
2
Order By: Relevance
“…In addition, intracellular accumulation of the anion, either by itself or in combination with intracellular acidification, can lead to toxic effects (Casal et al 1996;Eklund 1983;Pampulha and Loureiro-Dias 1990;Russell 1992). Benzoate, for instance, has been implicated in inhibition of autophagy (Hazan et al 2004) and acetate has been demonstrated to induce apoptosis (Ludovico et al 2001). Moreover, hydrolysates contain many compounds that act synergistically with organic acids.…”
Section: Common Inhibitors In Hydrolysates Effects and Mechanismsmentioning
confidence: 99%
“…In addition, intracellular accumulation of the anion, either by itself or in combination with intracellular acidification, can lead to toxic effects (Casal et al 1996;Eklund 1983;Pampulha and Loureiro-Dias 1990;Russell 1992). Benzoate, for instance, has been implicated in inhibition of autophagy (Hazan et al 2004) and acetate has been demonstrated to induce apoptosis (Ludovico et al 2001). Moreover, hydrolysates contain many compounds that act synergistically with organic acids.…”
Section: Common Inhibitors In Hydrolysates Effects and Mechanismsmentioning
confidence: 99%
“…[1,19,36] Therefore, while acetic acid may largely inhibit cells by generating a high intracellular pool of acetate anion and the lowering of intracellular pH (Figure 1b), the cytostatic effects of sorbic acid are suggested to be mainly due to its disordering of membrane structure. [2,36] High acetic acid is a potent inducer of yeast apoptosis; [6,[14][15][16] whereas the noted actions of benzoic and sorbic acids include a severe energy (ATP pool) depletion, [26] an inhibition of membrane trafficking, resulting in the arrest of macroautophagy [8] and, in the presence of oxygen, severe oxidative stress due to elevated endogenous production of reactive oxygen species (ROS) by a dysfunctional mitochondrial respiratory chain. [25] It is now known that acetic acid and sorbic acid, at these respective inhibitory concentrations, induce quite separate stress responses in pH 4.5 cultures of S. cerevisiae; one protective against acetic acid stress and another protective against the more lipophilic propionate, sorbate and benzoate (Table 1).…”
Section: A Brief Overview Of the Physiological Actions Of The Monocarmentioning
confidence: 99%
“…Yeasts are able to reduce the accumulation of weak acids inside the cells. The mechanisms of weak acid adaptation in yeasts are described in the studies of Brul and Coote (1999), Piper et al (2001), Hazan et al (2004).…”
Section: Growth Dynamics Of G Candidum In Co-culture With Fresco In mentioning
confidence: 99%